Bleeding and Thrombosis With Pediatric Extracorporeal Life Support: A Roadmap for Management, Research, and the Future From the Pediatric Cardiac Intensive Care Society. Issue 11 (November 2019) - Penk, Jamie S.; Reddy, Sushma; Polito, Angelo; Cisco, Michael J.; Allan, Catherine K.; Bembea, Melania; Giglia, Therese M.; Cheng, Henry H.; Thiagarajan, Ravi R.; Dalton, Heidi J.
Abstract : Objectives: To make recommendations on improving understanding of bleeding and thrombosis with pediatric extracorporeal life support including future research directions. Data Sources: Evaluation of literature and consensus conferences of pediatric critical care and extracorporeal life support experts. Study Selection: A team of 10 experts with pediatric cardiac and extracorporeal membrane oxygenation experience and expertise met through the Pediatric Cardiac Intensive Care Society to review current knowledge and make recommendations for future research to establish "best practice" for anticoagulation management related to extracorporeal life support. Data Extraction/Data Synthesis: This white paper focuses on clinical understanding and limitations of current strategies to monitor anticoagulation. For each test of anticoagulation, limitations of current knowledge are addressed and future research directions suggested. Conclusions: No consensus on best practice for anticoagulation monitoring exists. Structured scientific evaluation to answer questions regarding anticoagulation monitoring and bleeding and thrombotic events should occur in multicenter studies using standardized approaches and well-defined endpoints. Outcomes related to need for component change, blood product administration, healthcare outcome, and economic assessment should be incorporated into studies. All centers should report data on patient receiving extracorporeal life support to a registry. Abstract : Supplemental Digital Content is available in the text.